Anteseden Dari Brand Experience Serta Dampaknya Terhadap Urge to Buy Impulsively (Studi Pelanggan Uniqlo Pada Platform Social Commerce Di Wilayah Jabodetabek) - Tjhin Tania; Margaretha Pink (JURNAL ADMINISTRASI BISNIS, 2022)
The clothing industry experienced a decline in sales during the pandemic but the facts are different from PT Fast Retailing (UNIQLO) which based on research has increased sales in Indonesia during the pandemic, this has something to do with the success of their marketing strategy along with the different brand experiences they created. With this phenomenon, the aim of this research is to analyze the influence of the variables of convenience, user experience, promotion, product recommendation, brand experience, and urge to buy impulsively. This research model was modified from previous research by adding the brand experience variable. The results of the study explain the strongest positive relationship between convenience, product recommendation, and promotion toward brand experience, followed by user experience and promotion toward urge to buy impulsively. In addition, user experience has a significant effect on brand experience and brand experience also has a significant effect on impulse buying. This research was conducted with the number of research subjects 412 respondents who had shopped at UNIQLO through Instagram. Respondents were selected by purposive sampling and snowball sampling, while data collection was carried out using an online questionnaire. The research data were analyzed using the PLS-SEM 3.3.3 method. There are some managerial implications that can be suggested from this research.